2006
DOI: 10.1152/physiolgenomics.00094.2006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the bovine neutrophil transcriptome during glucocorticoid treatment

Abstract: The objective of this study was to characterize a large portion of the bovine neutrophil transcriptome following treatment with the anti-inflammatory glucocorticoid dexamethasone (Dex). Total RNA was isolated from blood neutrophils of healthy cattle (5 castrated male Holsteins) immediately following cell purification (0 h) or after ex vivo aging for 4 h with or without added Dex. Additional neutrophils were cotreated with a glucocorticoid receptor (GR) antagonist (RU486) and Dex for 4 h. RNA was amplified, dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…Some researcher showed no significant change of TLC after transportation compared to before in short duration (4 hours) of transportation. The proliferation of WBC in present study might be due to stimulating effects of glucocorticoids on white blood cells during long time transportation (Weber et al, 2007). The current study revealed that among the WBC the percentage of lymphocytes were decreased and the percentage of neutrophils was increased after transportation in comparison to before and 24h of post transportation.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 46%
“…Some researcher showed no significant change of TLC after transportation compared to before in short duration (4 hours) of transportation. The proliferation of WBC in present study might be due to stimulating effects of glucocorticoids on white blood cells during long time transportation (Weber et al, 2007). The current study revealed that among the WBC the percentage of lymphocytes were decreased and the percentage of neutrophils was increased after transportation in comparison to before and 24h of post transportation.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 46%
“…Differentially expressed genes fell into three major functional groups: immune function, apoptosis and wound healing. These expression changes largely correlated with the neutrophil count profile (Table 1), which relates to blood cortisol concentration in numerous models of bovine stress (Burton et al, 2005;Weber et al, 2006;Buckham Sporer et al, 2008). To our knowledge, this is the first study (Buckham Sporer et al, 2008) that has reported transportation-induced changes in the expression of key neutrophil inflammatory and antibacterial genes in association with peak cortisol and neutrophilia stress responses.…”
Section: Gene Expression Changes During Transportation Stressmentioning
confidence: 95%
“…Gene expression regulation results from the binding of cortisol to its GR in the cytoplasm of target cells, with subsequent translocation of hormone-activated receptors into the nucleus and modulation of gene transcription by direct (receptor-DNA) and indirect (receptor-protein-DNA) interactions in regulatory regions of cortisol-sensitive genes (Preisler et al, 2000;Weber et al, 2006). In addition, bovine neutrophils have been shown to exhibit differential expression of genes important to roles of immune function, apoptosis, tissue remodelling, and various metabolic and cellular functions in response to glucocorticoids in vitro and in vivo (Burton et al, 2005).…”
Section: Gene Expression Changes During Transportation Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils, crucial phagocytes for the acute defense of the lungs, respond to transportation stress by altering their numbers, migration capacity and function (Murata et al, 1987;Yagi et al, 2004). A large bulk of studies demonstrated that exogenously administrated or endogenously secreted glucocorticoids modulate the expression of neutrophil genes that regulate apoptosis, adhesion and inflammation Burton et al, 2005;Weber et al, 2001Weber et al, , 2006. In a recent study, Buckham Sporer et al (2007) showed that changes in concentrations of plasma cortisol might mediate the effect of transportation stress on altered expression of neutrophils.…”
Section: Lt-epoxide (% Of Lt)mentioning
confidence: 99%